Exercise physiology energy, nutrition, and human performance - McArdle, William D. 1939-; Katch, Frank I. 1942-; Katch, Victor L. 1945- (Lippincott Williams & Wilkins, 2007)
This textbook integrates basic concepts and relevant scientific information to provide a foundation for understanding nutrition, energy transfer, and exercise training. This new edition covers exercise physiology, uniting the topics of human performance, nutrition, energy expenditure and capacity, molecular biology, and more. Every chapter has been fully revised and updated to reflect the latest information. LiveAdvise online faculty support and student tutoring services are available free with the text. A bound-in CD-ROM contains questions to help students prepare for exams. A Connection Website provides additional faculty and student resources.